Ratio Decidendi of the Panel of Judges in Passing Judgement (Case Study of Case Decision No. 202/Pdt.G/2023/PN.Gin) - Putu Dyah Pramitha Dewi; I Gede Yusa (Transpublika Publisher, 2025)
This paper aimed to find out more deeply and understand the validity of debt and receivable agreements made by debtors and creditors with collateral for joint assets and to be able to find out and analyze the ratio of decisions of the Panel of Judges in handing down decisions. The method used is the normative research method, which uses several types of approaches, namely the case approach and the statute approach, the context of which is carried out by examining laws relating to legal issues. The results obtained from this research are that the debt and receivable agreement made by the parties in case Number 202/Pdt.G/2023/PN.Gin is not in accordance with the provisions of Article 36 paragraph (1) of Law No. 1 of 1974 concerning Marriage and ratio decidendi The Panel of Judges in this decision did not contain a legal basis explaining that the debt and receivable agreement made by the parties was legally valid.